Voting Control in German Corporations - BOEHMER, Ekkehart (Institutional Knowledge at Singapore Management University, 2003)
Corporate control in Germany has received considerable attention in the law and economics literature. However, the absence of disclosure provisions comparable to those of the Williams Act in the United States limited the informativeness of empirical studies. The recent transposition of the European Union’s Large Holdings Directive into German law allows us, for the first time, to analyze the voting power of blockholders in detail. We document that voting control is generally highly concentrated: about 82% of officially listed AGs have a minority blockholder (controlling more than 25% of the votes) and 65% are majority controlled. Blocks are clearly aligned with important control thresholds (25, 50, and 75%). We further show that important disclosure gaps remain. Banks (and other custodians) are exempt from disclosing the voting power they might derive from proxies or through their investment companies. As a result, banks and insurance companies only partially disclose the power they might have over blockholders and listed companies with (apparently) no blockholders. Finally, we provide a case-by-case analysis of disclosure filings and document the shortcomings of the new standard. Our findings suggest that corporate control is even more concentrated and that the influence of management-controlled entities is even larger than the disclosed voting-block statistics.